COMPARATIVE CRANIAL NONMETRIC STUDY OF ARCHAEOLOGICAL POPULATIONS FROM INNER ASIA - M.ERDENE (Mongolian Journal of Anthropology, Archaeology and Ethnology, 2008)
Results of the comparative cranial non-metric study of human remains unearthed in the territories of South Siberia, Altai, Buryatia and Inner Mongolia belonging to different historical periods, from Neolithic up to Mongolian (12-13th c AD) periods show general differentiation between populations from eastern Mongolia and Inner Mongolia on the one hand, and populations from Xingjian, Altai, South Siberia, Buryatia and western Mongolia on the other hand. Warring States and Bronze Age populations from Inner Mongolia, and Bronze Age Slab grave population from eastern Mongolia form a separate cluster. Position of Chandman population (with no coffin) from western Mongolia in this cluster might show a probable relationship of that population with the populations from eastern Mongolia or other regions in Inner Mongolia. Cluster analyses showed a picture of very heterogeneous population structure of inhabitants from Southern Siberia, Altai and Western Mongolia during Eoneolithic, Bronze and Early Iron Ages. Close relationship between Neolithic population from central Mongolia and Early Iron Age population from Xingjian; and between Neolithic Baikal, Chandman (with wooden chamber) from western Mongolia, and Afanasev from Altai Mountain indicate about their genetical affinities and biological continuity of those archaeological populations. Cluster analyses of 2nd BC to 8th AD period samples revealed very close characteristics for Xiongnu populations from Altai and Mongolia, and some similarity between Turkic from Altai and Han from Inner Mongolia. Comparative analysis of medieval period and contemporary populations from Baikalia, Buryatia, Mongolia, Inner Mongolia and Northeast Asia show more or less compact picture. Nevertheless, we can observe some tendencies in their biological affinities. Early Mongolians from Buryatia and Qidan from Inner Mongolia are closer to each other and Yuan population from Inner Mongolia and Amur and Korean contemporary populations are closer to each other. On the other hand Mongolian period populations from Mongolia and modern Buryats are very close to each other, and to some extent close to Northern Chinese. Modern Chinese are found very different from the other populations studied.